2019
DOI: 10.1177/0004867419879242
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological characteristics of subsyndromal depression in late life

Abstract: Objectives: Subsyndromal depression is prevalent and associated with poor outcomes in late life, but its epidemiological characteristics have barely been investigated. The aim of this prospective cohort study is to compare the prevalence, incidence and risk factors of subsyndromal depression with those of syndromal depression including major and minor depressive disorders in community-dwelling elderly individuals. Methods: In a nationwide community-based study of randomly sampled Korean elderly population aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 37 publications
1
16
0
8
Order By: Relevance
“…These results suggest that chronic/recurrent SSD with increasing severity may be a high-risk condition for dementia distinct from MCI, and our results are consistent with those of previous studies that reported that mild behavioral impairment, especially affective dysregulation, increases the risk of dementia in the psychiatric outpatient population (Ismail et al, 2016;Liew, 2020). Late in life, SSD is about 2.5 times more prevalent and has about five times greater incidence compared with clinically significant syndromal depression, such as MDD and mDD (Oh et al, 2019). More than half of the cases of SSD are chronic in both community (59-74%) (Beekman et al, 2002;Cohen et al, 2009) and primary care (51-70%) (Cui et al, 2008;Lyness et al, 2002Lyness et al, , 2009 settings.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These results suggest that chronic/recurrent SSD with increasing severity may be a high-risk condition for dementia distinct from MCI, and our results are consistent with those of previous studies that reported that mild behavioral impairment, especially affective dysregulation, increases the risk of dementia in the psychiatric outpatient population (Ismail et al, 2016;Liew, 2020). Late in life, SSD is about 2.5 times more prevalent and has about five times greater incidence compared with clinically significant syndromal depression, such as MDD and mDD (Oh et al, 2019). More than half of the cases of SSD are chronic in both community (59-74%) (Beekman et al, 2002;Cohen et al, 2009) and primary care (51-70%) (Cui et al, 2008;Lyness et al, 2002Lyness et al, , 2009 settings.…”
Section: Discussionsupporting
confidence: 92%
“…Third, the information about the degree of antidepressant exposure was limited, although several studies have identified the association between anticholinergic antidepressants and dementia risk (Coupland et al, 2019;Richardson et al, 2018). Finally, although the epidemiological and biological characteristics of SSD defined by our operational diagnostic criteria were well documented (Jeong et al, 2012;Oh et al, 2019;Park et al, 2015), the criteria need consensus from experts.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The diagnostic interview using the MINI-K was administered after the evaluations by trained research nurses and neuropsychological researchers with an interval of 1 week. We made a diagnosis of depressive disorder when a participant exhibited major or minor depressive disorders according to the Diagnostic and Statistical Manual of Mental Disorders, 4th edition (DSM-IV) criteria or subsyndromal depression according to the operational diagnostic criteria (Oh et al, 2020 ). The participants without any current depressive disorder and manic/hypomanic episode were defined as euthymic participants.…”
Section: Methodsmentioning
confidence: 99%